2012
DOI: 10.1016/j.joca.2012.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthritis-associated fibrosis is related with both elevated pyridinoline cross-link formation and lysyl hydroxylase 2b expression

Abstract: Purpose: Exosomes containing proteins, microRNAs and mRNAs are found in extracellular spaces such as blood and other body fluids and function as messengers in cell-cell communication through transfer of their molecular content. We hypothesize that exosomes containing miRNAs function in a novel communication mechanism among joint cells in osteoarthritis (OA) pathogenesis. We previously observed that the balance of anabolic and catabolic gene expression in chondrocytes was impaired by exosomes derived from OAsyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…OA is a disease of the articular joints in which synovial fibrosis is often seen (). Accumulating data have been presented to suggest that OA is an inflammatory disease in which cytokines and immune cells play a role ().…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…OA is a disease of the articular joints in which synovial fibrosis is often seen (). Accumulating data have been presented to suggest that OA is an inflammatory disease in which cytokines and immune cells play a role ().…”
Section: Discussionmentioning
confidence: 99%
“…These hydroxyallysine collagen crosslinks are found in fibrotic tissues and are associated with irreversible accumulation of collagen (). Recently, it was demonstrated that PLOD2 expression and the presence of LH2b are up‐regulated in the fibrotic synovium of mice with OA ().…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As alluded to earlier, stiffness may also be related, at least partially, to age‐related changes in material properties. It has been shown, both in man and horses, that in articular tissues certain cross‐links that for example are products of the so‐called nonenzymatic glycation process, such as pentosidine, or pyridinoline cross‐links, increase linearly with age once growth has ceased . These cross‐links would increase cartilage and soft tissue stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that these results are attributed to the 3D self-organized organoids maintaining a more chondrocyte-like phenotype compared with cells derived from 2D dish cultures ( Figure 2). Formation of fibrous tissue is the principal cause of joint pain and functional loss (Remst et al, 2013).…”
Section: Discussionmentioning
confidence: 99%